Sponsorship and fund‐raising in New Zealand schools: implications for health - Richards, R.; Darling, H.; Reeder, A.I. (Australian and New Zealand journal of public health, 2005)
Objective: To examine school participation in sponsorship, incentive and fundraising initiatives and to describe feedback about potential health implications and possible solutions from key stakeholders in the health and education sectors. Methods: All secondary/area schools and 15% of primary/intermediate schools were randomly selected from six geographical regions of New Zealand. School principals completed a self‐report questionnaire. Survey findings were summarised in a discussion document and forwarded to 53 key stakeholders for comment. Results: Most schools reported participation in sponsorship, incentive and fundraising initiatives (83% of primary/ intermediate and 85% of secondary/area schools). Some partnerships delivered positive health messages to students, but others were linked with products or activities potentially deleterious to health. Examples of the latter included provision of foods high in fat and sugar to students and funding from organisations whose profits were generated from gambling and alcohol sales. Key stakeholder concerns included the undermining of classroom health education and perceptions that schools were endorsing product consumption. Suggestions to address these concerns included increasing co‐ordination and awareness, alternative sources of funding, and policy guidelines or legislation. Conclusions: Most schools were involved in some sort of sponsorship, incentive and fundraising initiatives, some of which had the potential to have a negative impact on the health of students. Implications: There is an urgent need for co‐operation between the health and education sectors to ensure that these funding partnerships do not compromise student health.